Short‐term safety and efficacy of left atrial appendage closure with the WATCHMAN device in patients with small left atrial appendage ostia. (26th September 2017) - Venkataraman, Ganesh; Strickberger, S. Adam; Doshi, Shephal; Ellis, Christopher R.; Lakkireddy, Dhanunjaya; Whalen, S. Patrick; Cuoco, Frank
Abstract: Introduction: Left atrial appendage (LAA) closure with the WATCHMAN device, according to FDA labelling, is recommended in patients with a maximal LAA ostial width between 17 and 31 mm. The safety and efficacy of LAA closure in patients with a maximal LAA ostial width < 17 mm has not been evaluated. The goal of this study was to determine the acute and short‐term safety and efficacy of LAA closure with the WATCHMAN device in patients with a maximal LAA ostial width < 17 mm. Methods and results: Thirty‐two consecutive patients with a maximal LAA ostial width < 17 mm as determined by a screening transesophageal echocardiogram (TEE) underwent LAA closure with the WATCHMAN device between March 2015 and November 2016 at five medical centers, and were included in this study. Mean age, body mass index (BMI), and CHA2 DS2 ‐VASC score were 70.8 ± 8.6 years, 29.3 ± 6.5 kg/m 2, and 3.9 ±1.2, respectively. At the screening TEE, mean maximal LAA ostial width and depth were 15.6 ± 0.6 mm (range 14–16) and 23.2 ± 4.5 mm (range 13–31), respectively. Successful LAA closure with the WATCHMAN device was achieved in 31 of 32 patients (97%), with no major complications. TEE performed 45 days after LAA closure demonstrated no peridevice leak > 5 mm and no device related thrombi. Warfarin was discontinued in all 31 patients 45 days after LAA closure. Conclusions: LAA closure with the WATCHMAN device can be successfully and safely achieved in patients with a maximal LAA ostial width < 17 mm.